CD109, a novel TGF‐β antagonist, decreases fibrotic responses in a hypoxic wound model. Issue 7 (July 2014) - Winocour, Sebastian; Vorstenbosch, Joshua; Trzeciak, Alissa; Lessard, Lucie; Philip, Anie
Abstract Excessive extracellular matrix deposition that occurs in many fibrotic skin disorders such as hypertrophic scarring and scleroderma is often associated with hypoxia. CD109 is a novel TGF‐β co‐receptor and TGF‐β antagonist shown to inhibit TGF‐β‐induced extracellular matrix protein production in vitro. We examined whether CD109 is able to regulate extracellular matrix deposition under low oxygen tension in vivo using transgenic mice overexpressing CD109 in the epidermis. By creating dorsal bipedicle skin flaps with centrally located excisional wounds in these mice and their wild‐type littermates, we generated a novel murine hypoxic wound model. Mice were sacrificed on 7 or 14 days post‐wounding, and tissues were harvested for histological and biochemical analysis. Hypoxic wounds in both transgenic and wild‐type mice showed increased levels of HIF‐1α and delayed wound closure, validating this model in mice. Hypoxic wounds in CD109 transgenic mice demonstrated decreased collagen type 1 and fibronectin expression, and reduced dermal thickness on day 7 post‐wounding as compared to those in wild‐type mice and to non‐hypoxic control wounds. These results suggest that CD109 decreases extracellular matrix production and fibrotic responses during hypoxic wound healing. Manipulating CD109 levels may have potential therapeutic value for the treatment of fibrotic skin disorders associated with poor oxygen delivery.